2020
DOI: 10.3390/cancers12071770
|View full text |Cite
|
Sign up to set email alerts
|

FIGO 2018 Staging for Cervical Cancer: Influence on Stage Distribution and Outcomes in the 3D-Image-Guided Brachytherapy Era

Abstract: Recent widespread use of three-dimensional image-guided brachytherapy (3D-IGBT) has improved radiotherapy outcomes of cervical cancer dramatically. In 2018, the International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer was revised. However, the influence of the revisions on the stage distribution and outcomes of cervical cancers treated with 3D-IGBT remains unclear. Here, we retrospectively analyzed 221 patients with cervical squamous cell carcinoma treated with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Grigsby et al reported that 53% of patients had stage migration when the FIGO 2018 system was used [ 13 ]. Tomizawa et al noted that stage migration occurred in 53% of the patients from their single-institution study [ 14 ]. Our analysis identified that 59% of patients were upstaged: 4% to Stage IB3 and 48% to stage IIIC, with the other stages accounting for the rest when restaged using FIGO 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grigsby et al reported that 53% of patients had stage migration when the FIGO 2018 system was used [ 13 ]. Tomizawa et al noted that stage migration occurred in 53% of the patients from their single-institution study [ 14 ]. Our analysis identified that 59% of patients were upstaged: 4% to Stage IB3 and 48% to stage IIIC, with the other stages accounting for the rest when restaged using FIGO 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of para-aortic node (PAN) metastasis increases with the FIGO tumor stage [ 15 - 17 ]. For FIGO stages IB, II B, and III B disease, the risk of paraaortic node metastasis was about 5%, 20%, and 30%, respectively [ 14 - 16 ]. The presence of PANs was found to be the single most important independent predictor of relapse and survival in a multivariate analysis of 626 patients who were enrolled in Gynecologic Oncology Group (GOG) trials [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients in this study were followed up for at least 3 years; the median follow-up period exceeded 5 years. Multiple studies have analyzed the radiotherapy outcomes of cervical cancer by employing inclusion criteria compatible with those used for this study; these studies show that the onset of disease progression after 3 years post-radiotherapy is rare [ 15 , 47 , 48 ]. From this standpoint, the progression-free disease status and the resultant incidence of non-cancer specific SCC elevation identified in this study cohort is highly reliable.…”
Section: Discussionmentioning
confidence: 99%
“…1 Chemoradiotherapy is the standard definitive treatment for locally advanced cervical cancers. [2][3][4][5] On the other hand, addition of bevacizumab to the chemotherapy regimen (either cisplatin plus paclitaxel or topotecan plus paclitaxel) improves survival of those with recurrent or metastatic cancer. 6 The downside is that bevacizumab increases the risk of gastrointestinal fistula (by approximately 7% for Grade-2 or Grade-3 fistulas based on the Common Terminology Criteria for Adverse Events [CTCAE] version 3.0) in patients with a previous history of pelvic irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is the fourth most common cancer in women worldwide 1 . Chemoradiotherapy is the standard definitive treatment for locally advanced cervical cancers 2‐5 . On the other hand, addition of bevacizumab to the chemotherapy regimen (either cisplatin plus paclitaxel or topotecan plus paclitaxel) improves survival of those with recurrent or metastatic cancer 6 .…”
Section: Introductionmentioning
confidence: 99%